Hubungan Karbon Organik Terlarut dengan Sifat Tanah pada Toposekuen di Taman Nasional Bukit Duabelas: The Relationship of Dissolved Organic Carbon with Soil Properties on Toposequence in the Bukit Duabelas National Park - Syamsul Arifin; Arief Hartono; Kukuh Murtilaksono; Syaiful Anwar; Sunarti Sunarti; Yakov Kuztakov (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2017)
The organic matter in the forest ecosystem that contributes to the organic horizon of soil profile decomposes to CO2. The DOC (dissolved organic carbon) leached to the mineral soil horizons could be decomposed, leached or adsorbed onto mineral surfaces. The effect of soil properties on the DOC dynamic has not been fully understood because of limited data. The objective of this research was to characterize the DOC in Bukit Duabelas National Park and reveal the effect of soil profile position in toposequence and soil properties to the DOC. Six soil profiles were made with different positions in toposequence (two soil profiles on each upper, middle, and lower slope). Lysimeters were installed horizontally (in AO, AB and B horizons and in each soil profile) and connected to a bottle collector that placed on the bottom of the soil profile. The soil samples were collected from each of the soil profiles, at the beginning of the research, while soil solutions were collected periodically. The results showed that the independent sample t-test revealed that fluxes of DOC of soil profile on the lower slope were different from that of soil profiles on the upper and middle slopes. The concentration, amount, and fluxes of DOC in soil profile on the lower slope were higher than those of soil profiles on the upper and the middle slopes. The independent sample t-test also revealed that fluxes of DOC of AO horizons were different from those of AB and B horizons. The concentration, amount, and fluxes of DOC of AO horizon were higher than those of AB and B horizons. The result of Pearson correlation showed positive correlations between DOC fluxes with organic-C, total-N, and Cation Exchange Capacity (CEC), but negative correlation with soil bulk density, pH, and Fe dithionite-citrate-bicarbonate (Fed) content. The results suggested that soil profile on the lower slopes on toposequence had a higher amount of DOC than that on other soil profiles above it. Horizon AO had a higher amount of DOC than that of AB and B horizons. The increase of organic-C, total N and CEC increased DOC. On the other hand the increase of soil bulk density, pH and Fed decreased DOC. Keywords: DOC, horizon, soil organic matter, toposequence